Patient Health Questionnaire-9, Body Mass Index, Household Income According to Sleep Duration: Findings From a Community Health Survey - Jihyung Lee; Yoo Hyun Um; Jong-Hyun Jeong; Ho Jun Seo; Young-Chan Kim; Sung Hoon Yoon; Suk-Young Kim; Tae-Won Kim; Seung-Chul Hong (Sleep Medicine Research, 2023)
Background and Objective Research on the relationship between sleep duration and Patient Health Questionnaire-9 (PHQ-9), body mass index (BMI), and income in South Korea was scarce. This study aimed to investigate the relationship between sleep duration and the PHQ-9, BMI, and household income. Methods We used data from the Korean Community Health Survey (KCHS) conducted by the Korean Center for Disease Control and Prevention in 2018 which included a total of 228340 participants from across the country. We divided the participants into four groups based on their sleep duration and used one-way analysis of variance (ANOVA) to compare the mean values of PHQ-9, BMI, and household income among the groups. Results A total of 227899 respondents were included in the study. Based on a one-way ANOVA, the mean PHQ-9 score tended to increase as sleep duration decreased. However, the group with a sleep duration of 9 hours or more had an exceptionally higher mean PHQ-9 score than the group with a sleep duration of 7 to 9 hours. The BMI score generally decreased as the sleep duration increased. Additionally, the group with a sleep duration of 5 to 7 hours and 7 to 9 hours had higher household income than the group with a sleep duration of 5 hours or less or 9 hours or more. Conclusions This study demonstrated the association between sleep duration and PHQ-9, BMI, and household income. Sleep duration was found to be a factor influencing PHQ-9, BMI, and household income.